Development of submerged cultivation method for vaccine Mycoplasma mycoides subsp. mycoides strain - O. G. Lapteva (Ветеринария сегодня)
Membersof Mycоplasmagenusare widely spreadin nature (soil, water, manure, cereals, foodproducts), andthereareonespathogenic for humans, animals andbirds. Thegroupof highlydangerousdiseases includecontagiousbovinepleuropneumonia (CBPP) causedby Mycoplasma mycoides subsp. mycoides. Risk of the disease agent introduction to Russia with imported livestock and raw materials still remains. Therefore, of topical importance is the improvement of theCBPPvaccinemanufacturingtechnology. Thestudies wereaimedat thedevelopmentof themethodof thesubmergedcultivation of thevaccineMycoplasma mycoides subsp. mycoides strain. This methodallowsproduction of a large amountof thebiological material andsimplification of thebiologicalproduct manufacturingtechnology. Dynamicsof themycoplasmamassaccumulation duringthesubmergedcultivation wasexamined within thestudies. Fourphases of thebacterialgrowth wereclearlydemonstrated. Insignificantdecreaseof the microbial cell concentration was reportedin the first twodaysof cultivation; days 3 and 4 were specified by the increase of the microbial mass concentration by several orders of magnitude: from 2.5 × 108 to 4.5 × 109 cells/volume unit, on day 5 the concentration was in equilibrium and starting from day 6 the onset of the microorganism’s death phase was reported. Similar dynamics wasdemonstratedduringcultivation in thebioreactors. Singular friedegg-shapedcoloniesor their accumulations wereobservedat the visual examination of the submerged cultivated mycoplasma. Therefore, when using submerged cultivation method and such parameters as mycoplasma seeding at a dose of 105 microbial cells / volume unit; 2/3 filling volume; incubation at (37 ± 0.5) °С; agitation at 90 rpm and use of synthetic nutrient medium, the bacterium accumulatesat thetitreof 109 cell/volumeunit.